Parallel and Adaptive Simulation of Cardiac Fluid Dynamics - Griffith, Boyce E.; Hornung, Richard D.; McQueen, David M.; Peskin, Charles S. (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction The Immersed Boundary Method Parallel and Adaptive Implementation Simulating Cardiac Fluid Dynamics Conclusions and Future Work Acknowledgments References